Reliability analysis of power system with high penetration of solar power generation and new loads - Li, Xiaomeng (Nanyang Technological University, 2023)
In this dissertation, MATLAB is used for programming, IEEE-RBTS bus2 is selected as the test system, a simple mathematical model of solar power generation and a mathematical model of EVs are established, and the sequential Monte Carlo simulation method is used to assess the distribution network test system's reliability. By connecting solar power generation with different capacities to different nodes of the distribution network, it can be obtained that the reliability indices of the systemdrop as solar power generation capacity rises, therefore system reliability steadily increases. The impact of connecting solar power generation to various nodes will also vary; the impact of solar power generation on system reliability is more obvious in nodes with complicated grid structures and high load demands. The system reliability indices will significantly increase when EVs are connected to the test system, and the test system's reliability will certainly decrease as a result. As the number of EVs increases, this situation will be more significant; and when the power grid structure where the connected EVs are more complicated and the load demand is higher, the negative influence of EVs on the reliability of the test system will be more visible.